Sistem Informasi Monitoring Siswa Menggunakan SMS Gateway - Helvywidya Utari; Yaya Sudarya Triana (Ikatan Ahli Informatika Indonesia (IAII), 2019)
SMK Telkom Bandung is one of the educational institutions under the Telkom Education Foundation called Telkom Schools. As a school that has a mission to implement information system based on Information and Communication Technologies (ICT) for learning media, SMK Telkom Bandung must have an information system that can process student data related to student absences and grades. The management of absence and grade of student is not efficient because in once assesment process still requires a long time, there are a lot of errors in the sum result and data loss. Where these data are used to measure of the progress of student achievement. Therefore, it is necessary to develop a monitoring system for students who can deliver absent report and student grades to parents quickly through SMS Gateway notifications to help monitor the teaching and learning process in schools. This information system was developed using the SDLC prototype and PIECES analysis approach by integrating Gammu SMS Gateway as a notification feature. In the testing phase using black box testing the results show that the system can documentation absent and grades in a structured manner, be able to convey student attendance report information and grades quickly, teachers can present and evaluate attendance report and reports and grades accurately, as well as with the SMS Gateway notification parents can help monitor the teaching and learning process at school.